Detection of myocardial viability by low-dose dobutamine Cine MR imaging. - Sandstede, J; Bertsch, G; Beer, M; Kenn, W; Werner, E; Pabst, T; Lipke, C; Kretschmer, S; Neubauer, S; Hahn, D (1999)
The purpose of this work was to test the diagnostic value of dobutamine stress magnetic resonance imaging (MRI) for predicting recovery of regional myocardial contractility after revascularization. Cardiac wall motion abnormalities are due to either non-viable and/or scarred, or viable, but hibernating, myocardial tissue. Dobutamine stress leads to increased systolic wall thickening only in viable myocardium. Twenty-five patients with akinetic or dyskinetic myocardial regions were examined with a Cine FLASH-2D sequence at rest and during dobutamine stress (10 microg/kg/min). Patients were re-examined at rest 3, and in case of persisting wall motion defects, 6 months after revascularization. Criterion of viability was increasing end-systolic wall thickening during stress and/or at follow-up. Akinetic regions related either to the LAD (n = 19) or to the RCA (n = 6) were judged viable if > or = 50% of the affected segments improved. MR studies were completed in all subjects without arrhythmia or need for early terminations due to symptoms. Sensitivity, specificity, and positive predictive value for the prediction of myocardial viability were 61%, 90%, and 87% for the segment-related analysis, and 76%, 100%, and 100% for the patient-related analysis based on coronary artery distribution, respectively. Dobutamine stress MRI allows to predict global functional recovery of akinetic myocardial regions after revascularization with a high positive predictive value and high specificity.